Investigation of biosecurity risks associated with the feed delivery: A pilot study - Bottoms, Kate (Can Vet J, 2015)
This study explored potential biosecurity issues related to the delivery of feed to commercial farms. A pilot study was conducted to collect information about the day-to-day feed delivery, including biosecurity concerns at the level of the feed truck, the driver, and the farm. In addition, a reusable rubber boot was tested in an effort to increase the proportion of farms at which truck drivers wore clean footwear, and to explore an alternative to the standard plastic disposable boots that may be unsafe in winter conditions. Most farms did well in terms of proper dead-stock management and keeping the farm lane and feed bin areas clean. The provision of reusable rubber boots significantly increased the proportion of deliveries in which the driver wore clean footwear.